2013
DOI: 10.1631/jzus.b1200112
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMP-9 in hepatic sinusoidal obstruction syndrome induced by Gynura segetum

Abstract: Background and objective: Hepatic sinusoidal obstruction syndrome (HSOS) is characterized by painful hepatomegaly, ascites, increased body weight, and jaundice. Gynura segetum (Compositae), a plant widely used in Chinese traditional medicine, often leads to the development of HSOS. However, the mechanism is unclear. The aim was to study the role of matrix metalloproteinase-9 (MMP-9) in the onset of HSOS induced by Gynura segetum. Methods: Twenty-five male Sprague-Dawley rats were randomly divided into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…It has been shown to have anti-angiogenic [263] as well as antioxidative and anti-inflammatory properties [264]. Its medicinal use is risky though as there have been several reports of hepatic veno-occlusive disease linked to the consumption of G. segetum [265,266,267,268]. Liang and Roeder were the first to characterize senecionine from G. segetum [269].…”
Section: Occurrence Of Pyrrolizidine Alkaloids In Crop Plantsmentioning
confidence: 99%
“…It has been shown to have anti-angiogenic [263] as well as antioxidative and anti-inflammatory properties [264]. Its medicinal use is risky though as there have been several reports of hepatic veno-occlusive disease linked to the consumption of G. segetum [265,266,267,268]. Liang and Roeder were the first to characterize senecionine from G. segetum [269].…”
Section: Occurrence Of Pyrrolizidine Alkaloids In Crop Plantsmentioning
confidence: 99%
“…53 Although pre-HSCT conditioning therapy is the most common reason for developing SOS in the Western Hemisphere, in China, ingestion of PA-containing plants, such as G. segetum, frequently causes SOS in humans as well. 54 As a PA, G. segetum acts similarly to MCT, specifically by increasing MMP-9 levels, as shown in a study by Yu et al 43 (Table 5). More recently, a study by Qiu et al (2018) identified 18 metabolites, commonly found in urine and plasma, that can serve as potential diagnostic markers for G. segetuminduced hepatotoxicity.…”
Section: Gynura Segetummentioning
confidence: 69%
“…(MMP-9), for example, has been proposed to play a key role to regulate normal HC egression from BM (Lane et al, 2000). While production of MMP-9 by hepatic SECs has been reported (Yu et al, 2013), further studies will reveal whether BM SECs also produce MMP-9 and hence have any roles in egress of cells from BM. Taken together, BM SECs appear to be involved in regulation of cell egress from BM by providing adhesion molecules, chemokines, and possibly MMP-9 to the egressing cells.…”
Section: Expression Of Adhesion Molecules and Chemokinesmentioning
confidence: 99%